2007
DOI: 10.3354/dao01859
|View full text |Cite
|
Sign up to set email alerts
|

Sortase inhibitor phenyl vinyl sulfone inhibits Renibacterium salmoninarum adherence and invasion of host cells

Abstract: Renibacterium salmoninarum, the causative agent of bacterial kidney disease in salmonid fishes, is a Gram-positive diplococcobacillus belonging to the family Micrococcaceae. Analysis of the genome sequence of the bacterium demonstrated the presence of a sortase homolog (srtD), a gene specifying an enzyme found in Gram-positive bacteria and required for covalent anchoring of cell surface proteins. Interference of sortase activity is being examined as a target for therapeutic prevention of infection by several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…strain FB24, respectively. Using the tripartite pattern search method of Boekhorst et al (5), as well as tools such as Pfam, SignalP, TMpred, and ProDom, we identified seven ORFs in the R. salmoninarum ATCC 33209 genome specifying potential sortase substrates containing the LAxTG motif (RSal 33209_2105, RSal33209_3407, RSal33209_2525, RSal33209_ 3273, RSal33209_0619, RSal33209_1326, and RSal33209_ 0402), some of which were predicted to be cell surface proteinases or adhesins (62). Two of the seven potential SrtD substrates identified through bioinformatics analysis are annotated as products of pseudogenes (RSal33209_0619 and RSal 33209_1326), and the current search may have failed to identify additional complete sortase substrates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…strain FB24, respectively. Using the tripartite pattern search method of Boekhorst et al (5), as well as tools such as Pfam, SignalP, TMpred, and ProDom, we identified seven ORFs in the R. salmoninarum ATCC 33209 genome specifying potential sortase substrates containing the LAxTG motif (RSal 33209_2105, RSal33209_3407, RSal33209_2525, RSal33209_ 3273, RSal33209_0619, RSal33209_1326, and RSal33209_ 0402), some of which were predicted to be cell surface proteinases or adhesins (62). Two of the seven potential SrtD substrates identified through bioinformatics analysis are annotated as products of pseudogenes (RSal33209_0619 and RSal 33209_1326), and the current search may have failed to identify additional complete sortase substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of R. salmoninarum with sortase inhibitors decreases the adherence of R. salmoninarum to fibronectin and fish cells in vitro, suggesting that these proteins have a role in attachment (62). Recent drug discovery efforts have focused on sortases as a possible therapeutic target, and it is possible that such efforts will be important in preventing R. salmoninarum infection (62). While R. salmoninarum SrtD is the only apparent active sortase, the presence of a degenerate srtA gene and at least one degenerate SrtA substrate with homologs in Arthrobacter may represent additional examples of specific genome decay in a pathway not needed for the intracellular lifestyle of R. salmoninarum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infected fish may take months to show signs of disease. bacterial kidney disease is one of the most difficult bacterial diseases of fish to treat [108], mainly due to its ability to evade phagocytosis and invade and survive in host cells [109, 110]. R. salmoninarum is very slow growing, and it is extremely difficult to apply genetic manipulation techniques to study its gene functions.…”
Section: Renibacterium Salmoninarummentioning
confidence: 99%